Analysis of the pharmacological, phytochemical and microbiological profile of Brosimum gaudichaudii Trécul: A systematic review (Research, Society and Development, 2022)
Studies involving plants and their properties have been widely explored by scientists in recent years because of their curative potential and disease prevention. Among the various medicinal plants, Brosimum gaudichaudii Trécul, found in the Brazilian Cerrado, is considered a medicinal plant by the population. Thus, the present work proposes a bibliographic review of articles available in 2 databases, aiming to evaluate the pharmacological, phytochemical and microbiological parameters of ; B. gaudichaudii For the analysis of this study, 2 databases were selected, PubMed and Portal de Periódicos da CAPES, using the following keywords: Brosimum gaudichaudii; Brosimum gaudichaudii & pharmacological; Brosimum gaudichaudii & phytochemical; Brosimum gaudichaudii & microbiological, establishing as inclusion criteria only papers published in the last 10 years that outlined the predetermined profile of the plant. From 167 papers found, only 8 articles were selected for analysis after applying the exclusion and inclusion criteria. In general, the research showed that the pharmacological properties are employed in photochemotherapy for the treatment of melanogenic diseases, due to the presence of furanocoumarins. The hydroethanolic extract of the plant exhibited 18 bioactive components detected by HPLC ESI-MS technique. Finally, the parameters for the analysis of the antimicrobial properties against the inactivation of resistant bacteria and fungi, through in vitro studies, showed satisfactory results.